One-pass endovascular treatment of intracranial atherosclerotic stenosis with a novel PTA balloon and self-expanding microstent - Möhlenbruch, Markus Alfred; Pfaff, Johannes; Herweh, Christian; Bösel, Julian; Rizos, Timolaos; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Pham, Mirko (Neuroradiology, 2016)
IntroductionWe present a novel endovascular technique to treat intracranial atherosclerotic stenosis (ICS) with the specific potential to reduce the procedure-related complications which so far limited safety and efficacy of endovascular ICS intervention.MethodsSix consecutive patients were included in this study with the following criteria of inclusion: (1) failure of dual antiplatelet therapy defined as recurrent TIA or ischemic stroke, (2) presence of ICS of ≥70 %, and (3) endovascular accessibility of the target lesion as judged by CTA or MRA. Technical feasibility, safety, and efficacy were observed for the first-ballon-then-stent (FBTS) technique using the percutaneous transluminal angioplasty (PTA) balloon microcatheter over which a self-expandable microstent can be directly delivered obviating the need to exchange microcatheters.ResultsFBTS was performed in six patients (four female, median age 69, median stenosis 82.5 %) all refractory to best medical treatment: three V4, two M1, and one supraclinoid ICA stenosis. PTA and stent deployment were technically feasible in all patients and immediately effective with a median postprocedural stenosis grade of 10 %. Angiographic and clinical safety measures were met with no occult or clinically evident hemorrhage or ischemic complications (four patients discharged without alteration in mRS, two patients with significant clinical improvement). No occurrence of TIA, stroke, or death was observed during follow-up.ConclusionThe FBTS method in this series appeared to be safe and effective for the endovascular treatment of ICS. It bears the specific potential to reduce wire perforations, which so far have been linked to major procedure-related adverse events of endovascular ICS treatment.
Gesehen am 10.01.2018